Clinical profile of critically ill patients admitted with Dengue in a tertiary level hospital in Nepal: A retrospective study - Shrestha, Gentle Sunder; Pradhan, Akshay Prasad; Kharga, Satyam; Shrestha, Manjit; Lobsel, Tenzing; Raut, Birendra Kumar; Karki, Bal Chandra; Poudel, Nimesh; Gautam, Rakshya; Maharjan, Nisha (Journal of Advances in Internal Medicine, 2023)
BACKGROUND AND AIMS Dengue is a viral disease transmitted by mosquitoes. The burden of disease related to Dengue is considerable in tropical and sub-tropical countries. Recently, many countries observed the outbreak of Dengue. Our study aims to explore the clinical profile and outcome of the dengue positive cases admitted in the intensive care unit (ICU) of a tertiary level hospital in Lalitpur. METHODS We conducted a retrospective single center study in patients with proven Dengue, admitted to ICU. Data were collected between 20th August and 15th October 2022. Data collected were the baseline characteristics of patients, signs and symptoms and need for organ support. Patients were graded according to WHO severity scale. RESULTS A total of 31 cases were admitted during the study period. Fever, vomiting and malaise were the common presenting symptoms. Comorbidities like hypertension and diabetes were common. Hypotension, requiring inotropic support was present in nine (29.0%) of cases. Ten patients (32.3%) required respiratory support. Derange hepatic and renal function were common. Five patients (16.1%) presented with clinically significant bleeding. Six (19.4%) of the cases expired in ICU. Among the non-survivors, five (83.3%) had severe Dengue and one (16.7%) case had Dengue with warning signs. CONCLUSION Critically ill patients with Dengue have multisystem involvement. Severe Dengue and Dengue with warning signs is associated with significant morbidity and mortality.